Influence of Features of Interphase Boundaries on Mechanical Properties and Fracture Pattern in Metal–Ceramic Composites; Journal of Materials Science & Technology; Vol. 29, iss. 11 - Psakhie S. G. Sergey Grigorievich; Ovcharenko V. E. Vladimir Efimovich; Yu B.; Shilko E. V. Evgeny Viktorovich; Astafurov S.; Ivanov Yu. F. Yuriy Fedorovich; Byeli A.; Mokhovikov A. A. Aleksey Aleksandrovich (2013, 2013)
Title screen